PENGARUH KOMPETENSI, MOTIVASI DAN KINERJA KARYAWAN TERHADAP PENGEMBANGAN KARIR KARYAWAN DI KANTOR BPJS KETENAGAKERJAAN CABANG SOLOK - Febsri Susanti; Nofriyanti Nofriyanti (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
Public awareness about the need for social security in Indonesia is increasing day by day, especially for workers because in order to ensure that they can meet the basic needs of a decent life, financial problems, health problems and maintain the level of welfare. This study aims to determine the Effect of Competence, Motivation and Performance Employees Against Employee Career Development at BPJS Employment Office Solok Branch. Determination of the sample is done by sampling Saturated with the number of respondents as many as 30 employees. Data were collected through questionnaires and then analyzed descriptively and Independent-Sample T-Test with SPSS version 16 program. The results of data analysis showed that employee performance is the main factor in determining the level of career development. Meanwhile, Competence and Motivation have a not too dominant contribution to career development